2012
DOI: 10.2147/ijn.s34991
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cell-penetrating peptide-coated nanostructured lipid carriers on the oral absorption of tripterine

Abstract: Purpose: To develop nanostructured-lipid carriers (NLCs) coated with cell-penetrating peptides (CPP) for improving the oral bioavailability of tripterine. Methods: We prepared CPP-coated tripterine-loaded NLCs (CT-NLCs) by using a solvent evaporation method, and determined their physical properties. In vitro drug release was determined by using a dialysis bag diffusion technique, and intestinal toxicity was evaluated by performing MTT assay using Caco-2 cells. In vivo absorption was studied in an in situ rat i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Recently, cell penetrating peptides (CPP) have gained a lot of attention in the delivery of small molecules as well as macromolecules, liposomes and nanoparticles into cells by chemical modifications (Chen et al, 2012; Khafagy el and Morishita, 2012; Koren and Torchilin, 2012). CPPs act by transporting their cargoes into the cytoplasm via perturbation of the lipid bilayer of the cell membrane or by endocytosis (Trehin and Merkle, 2004; Zorko and Langel, 2005).…”
Section: Other Approaches To Enhance the Oral Delivery Of Peptide mentioning
confidence: 99%
“…Recently, cell penetrating peptides (CPP) have gained a lot of attention in the delivery of small molecules as well as macromolecules, liposomes and nanoparticles into cells by chemical modifications (Chen et al, 2012; Khafagy el and Morishita, 2012; Koren and Torchilin, 2012). CPPs act by transporting their cargoes into the cytoplasm via perturbation of the lipid bilayer of the cell membrane or by endocytosis (Trehin and Merkle, 2004; Zorko and Langel, 2005).…”
Section: Other Approaches To Enhance the Oral Delivery Of Peptide mentioning
confidence: 99%
“…However, it has been documented that modification of lipid nanoparticles for instance biotin attachment over their surface or charge modification promotes cellular uptake of nanoparticles via intestinal cells, overcoming the mucosal barrier that otherwise hinders their uptake [31,35]. Also, studies on cell-penetrating peptides (CPPs) coated over the surface of lipid nanoparticles are also based on the hypothesis that they will promote cross of intact nanoparticles across GIT, which gain access in systemic circulation where reticuloendothelial system (RES) system plays role [73]. However, in vivo studies on engineered NLCs are not satisfactory and there is necessity of detailed future studies to determine effects of composition, physiochemical properties and surface modification on the fate of lipid nanoparticles.…”
Section: Mechanism Of Nlcs Dispositionmentioning
confidence: 99%
“…Interesting studies using CPPs that can recognize specific receptors on GIT cells have allowed scientists to utilize them as an effective tool for oral delivery of various drugs. Although the exact mechanism of CPPs attached/coated lipid nanoparticles is unknown, but it has been considered that CPPs either encounters receptor mediated pathway, thus facilitating the internalization processes via endocytosis and translocation of attached nanoparticles or enter by disrupting the intestinal membrane [73]. In a study, in situ intestinal perfusion model performed in rats showed that peptide-coated NLCs markedly increased absorption of tripterine in the duodenum and jejunum in comparison to noncoated NLCs and tripterine suspension, in other words, 1.5- and 2.9-fold, respectively.…”
Section: Engineered Nlcsmentioning
confidence: 99%
See 1 more Smart Citation
“…The stability of optimized FT-CR NLC formulation could be attributed to the fact that FT was completely dissolved in the lipid matrix. (Zhang et al, 2010) Furthermore, Tween 80 and TPGS reduced the electrostatic repulsion between particles, leading to better stabilization and forming a layered structure around the particles (Zhou, 2012;Yuan et al, 2012).…”
Section: Caspase-3 Enzyme Assaymentioning
confidence: 99%